TOOLS FOR ENSURING THE ECONOMIC STABILITY OF DOMESTIC ENTERPRISES IN CONDITIONS OF TURBULENCE - IVANIUK, Ulana; MYKYTA, Nazariy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The study focuses on the critically difficult conditions of Ukraine’s business environment during the war, which significantly complicates not only the aspects of financial and economic efficiency, but its viability as a leading function of management. From such positions, the purpose of the research is to form a toolkit for ensuring the economic stability of domestic enterprises in turbulent conditions. It is shown that in the environment of a full-scale war and the critical turbulence caused by it, the issue of achieving the appropriate level of economic stability as the ability to counter the challenges, risks and threats of modernity has become relevant many times. The following managerial tasks for strengthening the economic viability of enterprises are indicated: (1) careful financial planning, (2) high-quality and balanced risk management, (3) optimization of financial resources, (4) permanent credit and financial monitoring, (5) tax planning. Approaches to the organization of the system for ensuring the economic sustainability of business are defined: strategic planning, technological innovations, management of intellectual and personnel support, continuous improvement, stakeholder approach. Leading measures that should be implemented in order to achieve the appropriate level of economic stability of domestic business entities in conditions of a high level of turbulence have been identified: (1) financial planning and budgeting, (2) cost rationalization, (3) risk management, (4) tax planning , (5) expansion of funding sources, (6) liquidity control, (7) improvement of management accounting and reporting.